Measurement of the tt̄ production cross section in pp̄ collisions at √s = 1.96 TeV in dilepton final states - Abazov, V. M. (2005)
We present a measurement of the top quark pair (tt̄) production cross section in pp̄ collisions at √s=1.96 TeV using events with two charged leptons in the final state. This analysis utilizes an integrated luminosity of 224-243 pb-1 collected with the DØ detector at the Fermilab Tevatron Collider. We observe 13 events in the e+e -, eμ and μ+μ- channels with an expected background of 3.2±0.7 events. For a top quark mass of 175 GeV, we measure a tt̄ production cross section of σtt̄=8. 6-2.7 +3.2(stat)±1.1(syst)±0.6(lumi) pb, consistent with the standard model prediction. © 2005 Elsevier B.V. All rights reserved.